Usefulness of Unilateral Nasal Packing for Recurred Septal Deviation within a Month after Septoplasty: Preliminary Study - Lee, Yoon Hee; Chang, Jin Soon; Jung, Joo Hyun; Kim, Seon Tae; Kang, Il Gyu (Journal of rhinology, 2019)
Background and Objectives: To investigate the effect of unilateral nasal packing on the correction of recurred septal deviationafter septoplasty. Materials and Method: We analyzed 12 patients who had undergone septoplasty and developed septal deviation recurrence. Polyvinylacetate and Vaseline gauze were inserted into the nasal passage on the convex side of the septum for 4 days in order toshift the septum to the midline. We analyzed nasal symptoms, acoustic rhinometric results, and endoscopic findings before andafter unilateral packing in order to evaluate the treatment outcomes. Results: Ten (83%) out of 12 patients showed improvements in nasal obstruction, acoustic rhinometric results, and endoscopicfindings. The mean visual analogue scale (VAS) score for nasal obstruction was 5.25±1.60 before and 2.08±1.50 after packing(p=0.004). The minimal cross-sectional area (MCA) improved from 0.17±0.14 to 0.27±0.13 (p=0.002), and the mean endoscopicscore improved from 2.0±0.43 to 1.08±0.29 (p=0.002). Conclusion: Unilateral nasal packing was a safe, easy, and effective method for correcting recurred septal deviation after septoplasty. KCI Citation Count: 0